Influence of electric field and current on the strength of depoled GaN piezoelectric semiconductive ceramics - Qin, G.; Ma, S.; Lu, Chunsheng; Wang, G.; Zhao, M. (Elsevier Science Ltd, 2017)
By using three-point bending tests, the effects of an applied DC electric field and current on the strength of depoled GaN piezoelectric semiconductive ceramics are investigated. Under combined mechanical-voltage-electrical current loading, the corresponding stress and electric fields and carrier distribution in specimens are analyzed based on the finite element method. It is shown that, when an electric field of 0.95kVcm -1 is applied, the bending strength decreases by 14.7% and then, remains unchangeable with further increase of the electric field. In contrast, the bending strength decreases from 11.5 to 8.5MPa as the applied electric current increases from 0 to 5 × 10 4 Am -2 . The results imply that there is a strong correlation between the bending strength and electric field or current for piezoelectric semiconductive ceramics.